2017
DOI: 10.1016/j.ijwd.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Compression stockings as an effective treatment for erythema nodosum: Case series

Abstract: Erythema nodosum (EN) is a septal panniculitis that is characterized clinically by tender, erythematous, subcutaneous nodules that are predominately localized on the pretibial lower legs. EN affects women more than men and can be idiopathic or secondary to another disease process such as infection or an immune response. Treatment options for erythema nodosum are suboptimal and often involve significant side effects or require a change in lifestyle. We investigated the effects of moderate 20 mmHg to 30 mmHg com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…Approximately 50% of EN cases are thought to be idiopathic with no cause found. 9 10 ENM is a rare variant and special type of EN, and was first described by Bafverstedt in 1954. 11 There have been few studies on ENM, and no case induced by valsartan has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of EN cases are thought to be idiopathic with no cause found. 9 10 ENM is a rare variant and special type of EN, and was first described by Bafverstedt in 1954. 11 There have been few studies on ENM, and no case induced by valsartan has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Bei 52 % der Patienten heilte die Wunde vollständig ab; insgesamt 71 % der Patienten konnten ein Selbstmanagement durchführen [27]. Es finden sich weitere Fallberichte zu entzündlichen Dermatosen der Beine bei den Diagnosen Erythema induratum [28], Erythema nodosum [29], Perifolliculitis capitis abscedens et suffodiens [30], Purpura pigmentosa progressiva [31], ulzerierende kutane Sarkoidose [32] und ulzerierende Morphea [33], die von einer Kompressionstherapie profitiert haben.…”
Section: Weitere Indikationenunclassified
“…11,25 It therefore has a firm place in the hitherto otherwise poorly standardized treatment approaches. 26 Casuistic descriptions are also available for erythema induratum, 27 erythema nodosum, 28 lichen ruber (verrucosus), 25 perifolliculitis capitis abscedens et suffodiens, 29 progressive pigmented purpura, 30 or scleroderma circumscripta. 31 Especially due to the frequently challenging pain symptoms, compression therapy in inflammatory dermatoses can be initiated with low resting pressure values of about 20 mmHg.…”
Section: Compression Therapy For Inflammatory Dermatosesmentioning
confidence: 99%